2018
DOI: 10.1016/j.chom.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccination Protects against Experimental Viral Infection in Humans through the Induction of Cytokines Associated with Trained Immunity

Abstract: The tuberculosis vaccine bacillus Calmette-Guérin (BCG) has heterologous beneficial effects against non-related infections. The basis of these effects has been poorly explored in humans. In a randomized placebo-controlled human challenge study, we found that BCG vaccination induced genome-wide epigenetic reprograming of monocytes and protected against experimental infection with an attenuated yellow fever virus vaccine strain. Epigenetic reprogramming was accompanied by functional changes indicative of trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,020
5
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 963 publications
(1,090 citation statements)
references
References 58 publications
48
1,020
5
17
Order By: Relevance
“…Similarly, a randomized control trial of BCG vaccination of low birth weight babies in Guinea‐Bissau suggested a reduction in infant mortality (mortality rate ratio = 83%; 95% CI 0.63–1.08%) driven by fewer cases of neonatal sepsis, respiratory infection and fever in the BCG‐vaccinated group. In a human yellow fever virus vaccine strain challenge study, BCG‐vaccinated volunteers had reduced viremia compared to non‐vaccinated participants . These findings are consistent with a variety of observational studies linking BCG vaccination and reduced risk of non‐mycobacterial infections, allergies, malignancies and all‐cause mortality .…”
Section: Clinical Effectiveness Of Bcgsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, a randomized control trial of BCG vaccination of low birth weight babies in Guinea‐Bissau suggested a reduction in infant mortality (mortality rate ratio = 83%; 95% CI 0.63–1.08%) driven by fewer cases of neonatal sepsis, respiratory infection and fever in the BCG‐vaccinated group. In a human yellow fever virus vaccine strain challenge study, BCG‐vaccinated volunteers had reduced viremia compared to non‐vaccinated participants . These findings are consistent with a variety of observational studies linking BCG vaccination and reduced risk of non‐mycobacterial infections, allergies, malignancies and all‐cause mortality .…”
Section: Clinical Effectiveness Of Bcgsupporting
confidence: 79%
“…Since innate responses are initiated by recognition of broadly conserved pathogen‐associated molecular patterns, BCG training induces stronger innate cytokine responses to both tuberculosis and other unrelated microorganisms. Consistent with this, the production of IL‐1β was correlated with reduction of yellow fever viremia in BCG‐vaccinated volunteers, whereas specific IFN‐γ production was not . Intriguingly, it was shown in mice that BCG vaccination could drive epigenetic changes in hematopoietic stem cells, potentially explaining how trained innate immunity can be effective over the long term …”
Section: Bcg‐induced Trained Innate Immunitymentioning
confidence: 59%
“…22 Blood was drawn before vaccination and 1 month later (see Supplementary material, Fig. Venous blood of healthy volunteers was drawn and genotyped after informed consent (Radboudumc, Nijmegen, the Netherlands).…”
Section: Blood Samplesmentioning
confidence: 99%
“…Six days after initial training, macrophages were restimulated with LPS. Previously it has been shown BCG‐induced trained immunity results in genome wide epigenetic reprogramming in vivo and up‐regulation of several cytokines. Pro‐inflammatory TNF‐α and IL‐6 and anti‐inflammatory IL‐10 were selected as example cytokines for our primary outcomes based on previous studies .…”
Section: Resultsmentioning
confidence: 99%